2000
DOI: 10.1111/j.1528-1167.2000.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Epilepsy With Occipital Paroxysms: Clinical Variants in 134 Patients

Abstract: Summary:Purpose: In its recent proposal, the Commission on Classification and Terminology of the International League Against Epilepsy classified childhood epilepsy with occipital paroxysms (CEOP) into two syndromes with different predominant seizure types: early onset (Panayiotopoulos type) with eye deviation and ictal vomiting and late onset (Gastaut type) with initial ictal visual symptoms. We documented the clinical features of a large group of patients with CEOP to confirm whether the classification is ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Panayiotopoulos et al (2012) stated that generalized paroxysms, as the sole EEG manifestation in children with PS, may occur in 4% of cases. In the most informative studies of patients with PS published, generalized paroxysms were found in 0% to 23.7% of cases (Ferrie et al, 1997;Oguni et al, 1999;Kivity et al, 2000;Verrotti et al, 2000;Lada et al, 2003;Ohtsu et al, 2003;Caraballo et al, 2007;Durá-Travé et al, 2008;Specchio et al, 2010). In the literature, no reports of patients with PS who had only generalized discharges on EEG at onset have been published.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Panayiotopoulos et al (2012) stated that generalized paroxysms, as the sole EEG manifestation in children with PS, may occur in 4% of cases. In the most informative studies of patients with PS published, generalized paroxysms were found in 0% to 23.7% of cases (Ferrie et al, 1997;Oguni et al, 1999;Kivity et al, 2000;Verrotti et al, 2000;Lada et al, 2003;Ohtsu et al, 2003;Caraballo et al, 2007;Durá-Travé et al, 2008;Specchio et al, 2010). In the literature, no reports of patients with PS who had only generalized discharges on EEG at onset have been published.…”
Section: Discussionmentioning
confidence: 99%
“…One year earlier, Panayiotopoulos (1988) had emphasized vomiting as an ictal symptom in epileptic seizures in children. Since then, important studies of children with this syndrome have been published (Caraballo et al, 1997(Caraballo et al, , 2000(Caraballo et al, , 2007Ferrie et al, 1997Ferrie et al, , 2006Oguni et al, 1999;Kivity et al, 2000;Verrotti et al, 2000;Lada et al, 2003;Covanis et al, 2003;Ohtsu et al, 2003;Durá-Travé et al, 2008;Specchio et al, 2010). The authors studied the variants of childhood epilepsies with occipital paroxysms (CEOP) based on a retrospective analysis of patients and confirmed the existence this earlyonset variant.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Kivity et al . () pointed out that 28% of their patients showed mixed signs and symptoms of both syndromes. In our study, 28% of the patients with pOLE, 20% of the patients with the typical autonomic symptoms of PS, and 21% of the patients with the typical visual symptoms of OLE‐G could not be classified as either PS or OLE‐G.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies on childhood OLE have indicated that many patients could not be classified as either PS or OLE-G. Genizi et al (2007) reported that half of their patients with occipital paroxysms could not be segregated into either specific syndrome. Kivity et al (2000) pointed out that 28% of their patients showed mixed signs and symptoms of both syndromes. In our study, 28% of the patients with pOLE, 20% of the patients with the typical autonomic symptoms of PS, and 21% of the patients with the typical visual symptoms of OLE-G could not be classified as either PS or OLE-G. With regard to the classification of OLEs, the most important factor in the literature appears to be the method of study.…”
Section: Discussionmentioning
confidence: 99%